Securing the commons: The UK Commons Act 2006 - Powell, John (2018)
John Powell POLICY SEMINAR The Future of the Commons Co-organized by IFPRI, the International Association for the Study of the Commons (IASC), and the CGIAR Research Program on Policies, Institutions, and Markets (PIM)